2022
DOI: 10.1186/s12877-022-03311-0
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and depressive symptoms in older Chinese: whether social isolation plays a role

Abstract: Background Existing evidence links hearing loss to depressive symptoms, with the extent of association and underlying mechanisms remaining inconclusive. We conducted a cross-sectional study to examine the association of hearing loss with depressive symptoms and explored whether social isolation mediated the association. Methods Eight thousand nine hundred sixty-two participants from Guangzhou Biobank Cohort Study were included. Data on self-reporte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Chia et al found a significant positive association between companionship SOSU and objective PA in Taiwanese men and women, but the association was stronger in women [ 113 ]. Huang et al found that walking together in a group significantly increased objective PA in older Taiwanese men [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chia et al found a significant positive association between companionship SOSU and objective PA in Taiwanese men and women, but the association was stronger in women [ 113 ]. Huang et al found that walking together in a group significantly increased objective PA in older Taiwanese men [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, middle-aged and elderly patients with HL were more likely to have diminished health status, depression, and suicidal ideation compared with participants without HL ( Park et al, 2022 ). Additional studies ( Chern et al, 2022 ; Huang et al, 2022 ) have suggested that HL can contribute to psychosocial disorders in patients. An MRI study revealed that gray matter volume in the middle cingulate cortex is positively correlated with high-frequency hearing impairment in patients with ARHL ( Ma et al, 2022 ).…”
Section: Sensory Deprivation Hypothesismentioning
confidence: 99%
“…The contact with relatives and friends was part of "nonface-to-face contacts (by telephone/mail)" from the Berkman-Syme Social Network Index (SNI), which has been validated in Chinese population [49]. We additionally included mail as another way of non-face-to-face contact besides telephone, since both telephone and mail were common non-face-to-face contact ways in 2003, before smartphone, Internet, and social media had become popular [50,51]. According to the previous GBCS papers, the contact with relatives and friends were categorized into not at all, <once/month, ≥once/month, ≥once/week, or almost daily [50][51][52].…”
Section: Potential Confoundersmentioning
confidence: 99%
“…We additionally included mail as another way of non-face-to-face contact besides telephone, since both telephone and mail were common non-face-to-face contact ways in 2003, before smartphone, Internet, and social media had become popular [50,51]. According to the previous GBCS papers, the contact with relatives and friends were categorized into not at all, <once/month, ≥once/month, ≥once/week, or almost daily [50][51][52]. Other data included subjective health status as good or poor, and history of chronic diseases (including hypertension, diabetes, cancer, chronic obstructive pulmonary disease, and coronary heart disease) based on physical examination and self-reported previous physician diagnoses or medication history, which was categorized into none and yes (one or more).…”
Section: Potential Confoundersmentioning
confidence: 99%